2019
DOI: 10.3390/ma12203337
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Traffic Vibrations on the Flexural Properties of Newly Placed PVA-ECC Bridge Repairs

Abstract: Polyvinyl alcohol fiber reinforced engineering cementitious composites (PVA-ECCs) exhibit excellent tight-cracking and super-high toughness behaviors and have been widely used in bridge repair projects. In reality, the conventional method in bridge repair is that a portion of the bridge is closed and repaired while the other portion is left open to traffic. Consequently, newly placed PVA-ECC bridge repairs (NP-ECC-BRs) are exposed to continuous traffic vibrations (TRVs), even during the setting periods. Howeve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…More recent investigations showed that vehicle-induced vibrations tend to negatively affect cementitious composites in general. For example, they negatively affect both the tensile performance of early-age polyvinyl alcohol-engineering cementitious composites (PVA-ECCs) [12] and the flexural strength of newly placed PVA-ECCs [13].…”
Section: Introductionmentioning
confidence: 99%
“…More recent investigations showed that vehicle-induced vibrations tend to negatively affect cementitious composites in general. For example, they negatively affect both the tensile performance of early-age polyvinyl alcohol-engineering cementitious composites (PVA-ECCs) [12] and the flexural strength of newly placed PVA-ECCs [13].…”
Section: Introductionmentioning
confidence: 99%
“…Polyvinyl alcohol fiber-reinforced engineering cementitious composites (PVA-ECCs) are proposed in another paper [ 12 ], where the authors address the challenge of closing and repairing a portion of a bridge while the other portion is left open to traffic. Consequently, newly placed PVA-ECC bridge repairs (NP-ECC-BRs) are exposed to continuous traffic vibrations (TRVs), even during the setting periods.…”
mentioning
confidence: 99%